Educação especial e formação inicial no contexto regional do Amazonas - Menezes Menezes, Reinaldo Oliveira; Picanço Simas, Hellen Cristina (Transformación, 2024)
Objective: This article aims at contextualizing special education as a challenge for the State of Amazonas in the last decades, especially in teachers’ education to train graduates to face the new demands posed by students with special educational needs in public schoolsMethods: The author relies on documentary review to study the Brazilian legislation on special education, inclusion, and initial teacher training. He examines research reports and publications and surveys the Pedagogical Course Program of undergraduate courses from public and private universities in the State of Amazonas.Result: The findings showed that a single university (out of eight sampled) has included special education contents in the curriculum of Pedagogical Course Program.Conclusions: The challenge in the regional context is to [rethink] teacher training based on the inclusion policy movement, since there is no doubt that there is a need to prepare teachers for a new school reality. This will happen when we restructure the pedagogical projects of the courses guiding teachers’ education.
Keywords: Special education; inclusion; initial teachers’ training